2020
DOI: 10.29252/ibj.24.2.99
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hair Follicle Stem Cells on Partial-Thickness Burn Wound Healing and Tensile Strength

Abstract: Background: The recent improvements in wound healing have led to new strategies in regenerative medicine. Burn wound healing is an important issue in skin regeneration and has multiple indications for stem cell therapy. HFSCs are a highly promising source of stem cells for healing use, as these cells are accessible, active and pluripotent adult stem cells. Methods: HFSCs of the rat whisker were isolated, cultured, and labeled with DiI. Flow cytometry method was used to detect special markers of HFSCs. Deep par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 21 publications
0
40
0
1
Order By: Relevance
“…Fourteen studies [ 16 , 28 , 29 , 37 39 , 41 , 44 50 ] used rats, six studies [ 17 , 30 , 40 , 42 , 43 , 51 ] used mice, and two studies [ 36 , 52 ] used minipigs. A total of 10 studies were conducted in China [ 29 , 30 , 37 , 39 , 40 , 43 , 47 49 , 51 ], 3 studies in Brazil [ 16 , 28 , 41 ], 3 studies in the USA [ 36 , 42 , 52 ], and 2 studies in Iran [ 38 , 45 ], whereas the remaining 4 were conducted in Pakistan [ 46 ], Egypt [ 44 ], Turkey [ 50 ], and Canada [ 17 ], respectively. Four studies [ 40 , 43 , 48 , 51 ] did not report burn degree and two [ 38 , 45 ] used second-degree burns, while the others used third-degree.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen studies [ 16 , 28 , 29 , 37 39 , 41 , 44 50 ] used rats, six studies [ 17 , 30 , 40 , 42 , 43 , 51 ] used mice, and two studies [ 36 , 52 ] used minipigs. A total of 10 studies were conducted in China [ 29 , 30 , 37 , 39 , 40 , 43 , 47 49 , 51 ], 3 studies in Brazil [ 16 , 28 , 41 ], 3 studies in the USA [ 36 , 42 , 52 ], and 2 studies in Iran [ 38 , 45 ], whereas the remaining 4 were conducted in Pakistan [ 46 ], Egypt [ 44 ], Turkey [ 50 ], and Canada [ 17 ], respectively. Four studies [ 40 , 43 , 48 , 51 ] did not report burn degree and two [ 38 , 45 ] used second-degree burns, while the others used third-degree.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies [ 40 , 43 , 48 , 51 ] did not report burn degree and two [ 38 , 45 ] used second-degree burns, while the others used third-degree. The cell types used for transplantation were mesenchymal stem cells (MSCs) [ 17 , 28 30 , 43 – 48 , 50 ], epidermal stem cells (ESCs) [ 40 , 51 ], hair follicle stem cells (HFSCs) [ 38 ], stromal vascular fraction (SVF) [ 36 , 52 ], and adipose-derived stem cells (ASCs) [ 16 , 37 , 39 , 41 , 42 , 49 ]. As for mesenchymal stem cells, they derived from umbilical cord [ 30 , 46 – 48 ], bone marrow [ 28 , 29 , 43 – 45 , 50 ], and burned tissue [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, only small and superficial wounds are suitable for spray therapy. Topical application and injection of hSCs have been conducted in both rat models and ulcer patients, and it showed better wound closure by reducing inflammation and improving epithelialization and angiogenesis [50][51][52]. The administration of SCs not only accelerates wound healing, but also enhances the physiological function of skin.…”
Section: Therapeutic Strategies Targeting Epidermal Scs and Relevant mentioning
confidence: 99%
“…19 Beyond the cell types mentioned above, hair follicles contain a number of stem cells at their base that play a role in wound healing. [20][21][22] Si et al found that transfecting hair follicle stem cells with the lncRNA PlncRNA-1 increased their proliferation and differentiation. Treatment of these transfected cells with the TGF-β1 inhibitor LY2109761 decreased these effects, suggesting a role for PlncRNA-1 in the TGF-β1-mediated Wnt/β-catenin signaling cascade.…”
Section: Integumentary Systemmentioning
confidence: 99%
“…Beyond the cell types mentioned above, hair follicles contain a number of stem cells at their base that play a role in wound healing 20‐22 . Si et al found that transfecting hair follicle stem cells with the lncRNA PlncRNA‐1 increased their proliferation and differentiation.…”
Section: Therapeutic Activity Of Lncrna For Tissue Repair and Regenermentioning
confidence: 99%